Numerical study of hydrodynamic impact on bubbly water - ELHIMER, Mehdi; EL MALKI ALAOUI, Aboulghit; CROCI, Kilian; GABILLET, Céline; JACQUES, Nicolas (ASME, 2015)
The phenomenon of slamming on a bubbly liquid has many occurrences in marine and costal engineering. However, experimental or numerical data on the effect of the presence of gas bubbles within the liquid on the impact loads are scarce and the related physical mechanisms are poorly understood. The aim of the present paper is to study numerically the relationship between the void volume fraction and the impact loads. For that purpose, numerical simulations of the impact of a cone on bubbly water have been performed using the finite element code ABAQUS/Explicit. The present results show the diminution ofthe impact loads with the increase of the void fraction. This effect appears to be related to the high compressibility of the liquid-gas mixture. The phenomenon of slamming on a bubbly liquid has many occurrences in marine and costal engineering. However, experimental or numerical data on the effect of the presence of gas bubbles within the liquid on the impact loads are scarce and the related physical mechanisms are poorly understood. The aim of the present paper is to study numerically the relationship between the void volume fraction and the impact loads. For that purpose, numerical simulations of the impact of a cone on bubbly water have been performed using the finite element code ABAQUS/Explicit. The present results show the diminution ofthe impact loads with the increase of the void fraction. This effect appears to be related to the high compressibility of the liquid-gas mixture.